Efficiency of Production Factor Use in Cabbage Farming in Banyuroto Village, Sawangan Sub-District, Magelang DistrictS - Sriyadi, Sriyadi; Putri, Tasya; Isnawan, Bambang (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Banyuroto Village is located in a hilly area in Sawangan District, Magelang Regency so it is very suitable for cabbage horticulture farming. We conducted this study to analyze the factors affecting production in Banyuroto Village and the efficiency of using these factors. We conducted a census on three farmer groups in Kenayan and Grintingan hamlets, resulting in a total sample of 80 farmers. The method used is a quantitative approach using Cobb-Douglas type production function analysis. The analysis of cabbage farming showed that the variables of land area, seeds, manure, phonska fertilizer, HNO fertilizer, Calcium fertilizer, solid pesticides, liquid pesticides, and labor had a significant effect on cabbage production. Partially, seeds, phonska fertilizer, and labor production factors affect cabbage production. To analyze the efficiency of the use of production factors, labor production factors in its use is efficient. Contribution to Sustainable Development Goals (SDGS):SDG 1: No Poverty SDG 2: Zero HungerSDG 12: Responsible consumption and production      SDG 13: Climate Action